Analysis of The Influence of Fintech on The Adoption Rate of Digital Financial Services - Hidayat, Rahmat; Faradina, Anggia (Nomico, 2025)
This study aims to analyze the impact of fintech on the adoption rate of digital financial services in Indonesia. In recent years, the development of financial technology (fintech) has brought significant changes to the financial system, particularly in terms of accessibility, efficiency, and convenience of financial services for the public. This research employs a quantitative approach using a survey method involving several respondents who are users of fintech services, and the data were analyzed using SPSS software to examine the relationships between variables. The findings reveal that ease of use, trust in the platform, and service innovation have a significant and positive influence on the adoption rate of digital financial services. On the other hand, cost efficiency is not a primary factor, although it still contributes to users' decision-making. Financial and digital literacy also support adoption, although they are not dominant variables. The study concludes that to enhance the widespread adoption of fintech, an integrated effort is needed through education, improved system security, and the development of features tailored to local needs. These findings are expected to serve as input for fintech developers, regulators, and other stakeholders in building an inclusive and sustainable digital financial ecosystem.